2018
DOI: 10.1111/coep.12394
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Brewing: Homebrewing Legalization and the Brewing Industry

Abstract: In 1978, H.R. 1337 was signed into Federal law allowing for the home production of beer at the national level forever changing the U.S. brewing industry. Like the repeal of Prohibition, states were granted the right to enact their own homebrewing laws, resulting in a heterogeneous rollout of legalized homebrewing. This research examines the relationship between homebrewing legislation and the growth of the beer industry across the United States, and finds that enacted legislation has had a significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In conclusion, the government's aim to support small scale beer production has been successful because it helped the survival of the Hungarian microbreweries. In general, Hungarian results also underline the importance of supportive governmental attitude, because similar to other countries (e.g., in the USA [5]), microbreweries are highly dependent on regulation, and on taxation in particular.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In conclusion, the government's aim to support small scale beer production has been successful because it helped the survival of the Hungarian microbreweries. In general, Hungarian results also underline the importance of supportive governmental attitude, because similar to other countries (e.g., in the USA [5]), microbreweries are highly dependent on regulation, and on taxation in particular.…”
Section: Discussionmentioning
confidence: 66%
“…The craft beer revolution began in the United States, after the strict alcohol ban and, since 1978, the Federal Law has allowed home brewing. McCullough et al [5] examined the relationship between home brewing legislation and the beer industry in the United States and found that the new legislation significantly impacted the industry's structure and growth. Previous studies suggested that craft beers have spread around the world for very different reasons.…”
Section: Introduction 1introductionmentioning
confidence: 99%
“…On this topic, studies by, for example, Cabras and Higgins (2016), Williams (2017), and Cappellano and Spisto (2019), highlight how policy changes have been made to support entrepreneurs in the craft beer sector, thus enabling further growth in the sector. Examples of this include removing restrictions and legalising home brewing in the US in 1979, contributing to the evolving of a viable business sector (Mccullough et al, 2018;Nilsson et al, 2018). Cappellano and Spisto (2019) illustrate how a political climate friendly to the craft beer industry has triggered the US movement through tax incentives and even grants in San Diego, which has allowed the number of breweries to grow.…”
Section: The Evolution Of the Craft Beer Sectormentioning
confidence: 99%
“…The beer market changed significantly in 1979 when changes in federal laws freed states to allow for homebrewing [13]. Over the next few decades, many of those hobbyists set out to commercialize their homebrews, planting the seeds of a burgeoning craft beer market [16].…”
Section: Introductionmentioning
confidence: 99%